A nitrogen / sulfur co-doped sodium alginate-based porous carbon material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611351606.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]然而,现有生物质衍生多孔碳在实际应用中仍存在一些问题,如前驱体组成复杂、结构不均一,导致碳化后孔结构紊乱;传统掺杂方法存在组分分离及杂原子流失现象,导致后续掺杂不均和结构坍塌;多使用强腐蚀性活化剂构筑多级孔结构,刻蚀过程剧烈且不可控,易过度烧蚀、形成死孔等
(1)本发明使用的海藻酸钠是一种环境友好、成本低的生物质资源,其表面含有丰富的羟基、羧基等官能团,与木质素磺酸钠中的羟基及天然硫源磺酸钠基团,以及活化剂(碳酸钾和一水合草酸铵)通过氢键、静电引力等非共价相互作用在水溶液中进行自组装,实现了“碳源-氮/硫源-活化剂”的高度有序组装与分子水平均匀融合,从源头上克服了物理混合导致的组分分离问题,为后续分级孔隙构筑与杂原子原位均匀掺杂奠定结构基础。
Smart Images

Figure CN122897407A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy materials technology, and in particular to a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, its preparation method, and its application. Background Technology
[0002] With the energy transition, high-performance energy storage devices have become a research hotspot. Supercapacitors (SCs) have broad application prospects due to their advantages such as high power density, fast charge and discharge speed, and long cycle life. Electrode materials, as the core carriers for charge storage and transfer in supercapacitors, directly determine their energy storage performance and lifespan through their physicochemical properties and microstructure. The charge storage mechanism of supercapacitors is based on double-layer capacitance and pseudocapacitance. Double-layer capacitance is mainly related to the specific surface area and pore structure characteristics of the electrode material, while pseudocapacitance is closely related to heteroatom doping and the type of functional groups on the electrode surface. Carbon materials are considered one of the ideal electrode materials due to their high specific surface area, low cost, good conductivity, and stable chemical properties.
[0003] However, existing biomass-derived porous carbon still faces several challenges in practical applications. For example, the complex composition and heterogeneous structure of the precursors lead to disordered pore structures after carbonization; traditional doping methods suffer from component separation and heteroatom loss, resulting in uneven subsequent doping and structural collapse; and the use of highly corrosive activators to construct hierarchical porous structures results in a violent and uncontrollable etching process, prone to over-etching and the formation of dead pores. Therefore, developing high-performance biomass porous carbon materials with controllable structures and uniform heteroatom doping is of significant research importance for promoting the green and low-carbon transformation of the energy sector. Summary of the Invention
[0004] The purpose of this invention is to address the existing technical deficiencies in carbon materials for supercapacitors by providing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, its preparation method, and its applications. This invention utilizes a supramolecular self-assembly-assisted bidirectional pore-forming strategy. The hydroxyl and carboxyl groups on the sodium alginate molecular chain, along with the hydroxyl groups in sodium lignin sulfonate and the natural sulfur source sodium sulfonate groups, undergo self-assembly in an aqueous solution with a subsequently introduced activator through non-covalent interactions such as hydrogen bonding and electrostatic attraction. The resulting material, with a hierarchical porous structure, is then prepared through a two-step carbonization-activation process.
[0005] To achieve the above objectives, the present invention provides a method for preparing nitrogen / sulfur co-doped sodium alginate-based porous carbon materials, comprising the following steps: S1. Sodium alginate, sodium lignosulfonate and water are mixed and stirred for the first time. Potassium carbonate and ammonium oxalate monohydrate are added and stirred for the second time. The mixture is then freeze-dried to obtain sodium alginate-based carbon precursor. S2. Under a nitrogen atmosphere, the sodium alginate-based carbon precursor is carbonized, activated, washed, and dried to obtain nitrogen / sulfur co-doped sodium alginate-based porous carbon material.
[0006] Preferably, in S1, the mass-volume ratio of sodium alginate, sodium lignosulfonate, and water is 30 mg: 30 mg: 2 mL, and the mass ratio of sodium alginate, potassium carbonate, and ammonium oxalate monohydrate is 1: (1-4): (1-4).
[0007] Preferably, in S1, the temperature of the first stirring is 50-70℃ and the stirring time is 0.1-1h; the temperature of the second stirring is 50-70℃ and the stirring time is 2-3h.
[0008] Preferably, in S1, the freeze-drying temperature is -56°C and the freeze-drying time is 48 hours.
[0009] Preferably, in S2, the carbonization temperature is 300-500℃, the carbonization time is 0.1-1h, and the carbonization heating rate is 3-10℃·min. -1 .
[0010] Preferably, in S2, the activation temperature is 600-800℃ and the activation time is 1-3h.
[0011] Preferably, in S2, the flow rate of nitrogen is 10-150 mL·min. -1 .
[0012] The present invention also provides a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, which is prepared by the above-described preparation method.
[0013] This invention also provides an application of a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, wherein the aforementioned nitrogen / sulfur co-doped sodium alginate-based porous carbon material is applied to a supercapacitor electrode material. The preparation method of the supercapacitor electrode material includes the following steps: Step 1: Mix the prepared nitrogen / sulfur co-doped sodium alginate-based porous carbon material, conductive carbon black, and binder in a mass ratio of 8:1:1. Add a small amount of ethanol, grind, roll, and dry to obtain a conductive carbon film of uniform thickness. Load the carbon film onto the treated nickel foam surface and compact it under a pressure of 10 MPa to obtain the working electrode. Step 2: Using the two electrodes with the same active material loading as the working electrodes, apply 6 mol·L⁻¹ water. -1 KOH is used as the electrolyte to assemble a sandwich-structured symmetrical supercapacitor.
[0014] Therefore, the present invention employs the above-mentioned nitrogen / sulfur co-doped sodium alginate-based porous carbon material, its preparation method, and its application, which have the following beneficial effects: (1) The sodium alginate used in this invention is an environmentally friendly and low-cost biomass resource. Its surface contains abundant functional groups such as hydroxyl and carboxyl groups. It self-assembles with the hydroxyl groups in sodium lignosulfonate, the natural sulfur source sodium sulfonate groups, and the activator (potassium carbonate and ammonium oxalate monohydrate) in aqueous solution through non-covalent interactions such as hydrogen bonding and electrostatic attraction. This achieves highly ordered assembly and uniform fusion at the molecular level of "carbon source-nitrogen / sulfur source-activator", which overcomes the component separation problem caused by physical mixing from the source and lays a structural foundation for subsequent hierarchical pore construction and in-situ uniform doping of heteroatoms.
[0015] (2) This invention uses potassium carbonate and ammonium oxalate monohydrate as composite activators. Ammonium oxalate monohydrate serves as a highly efficient nitrogen source, and at the same time, it decomposes under medium and low temperature pyrolysis to produce gases such as CO2 and NH3, exerting a strong "inward gaseous pore-forming" effect. Meanwhile, potassium carbonate plays an "outward chemical etching" role at high temperatures, generating a unique "bidirectional pore-forming" synergistic mechanism. This gas-solid dual-phase linkage completely solves the problem of low pore-forming efficiency of a single activator, successfully constructing a through-type hierarchical pore structure with "macropores as transport centers, mesopores as transport channels, and micropores as energy storage sites," realizing the synergistic linkage of "one agent for two uses" and "doping-pore-forming."
[0016] (3) The nitrogen / sulfur co-doped sodium alginate-based porous carbon material prepared by this invention has a high specific surface area (up to 1961 m²). 2 ·g -1 The well-developed hierarchical porous structure and high microporosity (micropore volume above 62%), along with the high specific surface area, are conducive to charge storage and accumulation, while the hierarchical pore structure facilitates rapid ion transport and charge storage in the electrolyte.
[0017] (4) Based on the above structural advantages, the nitrogen / sulfur co-doped sodium alginate-based porous carbon material prepared in this invention exhibits excellent electrochemical performance at 0.5 A·g -1 The specific capacitance can reach 427 F·g at current density. -1 This is because the uniform mixing of raw materials at the molecular level and the synergistic doping of heteroatoms effectively improve the structure of carbon materials and increase the specific capacitance of electrode materials.
[0018] (5) A carbon electrode was prepared using the nitrogen / sulfur co-doped sodium alginate-based porous carbon material prepared in this invention, with a concentration of 6 mol·L⁻¹. -1 Using KOH as the electrolyte, a symmetrical supercapacitor was assembled at 0.5 A·g. -1 At a current density of 225 W·kg, the device power density is 225 W·kg. -1 With an energy density as high as 14.96 Wh·kg -1 In 10A·g -1After undergoing 50,000 charge-discharge cycles at high current density, the capacity retention rate reached 83.89%. The results confirm that this material can be used as an electrode material for supercapacitors and has significant prospects for industrial application.
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0020] Figure 1 This is a scanning electron microscope image of the nitrogen / sulfur co-doped sodium alginate-based porous carbon material of Example 1 of the present invention; Figure 2 These are nitrogen adsorption-desorption isotherm curves of nitrogen / sulfur co-doped sodium alginate-based porous carbon materials in Examples 1-5 of this invention; Figure 3 These are pore size distribution diagrams of the nitrogen / sulfur co-doped sodium alginate-based porous carbon materials in Examples 1-5 of this invention; Figure 4 These are the constant current charge-discharge curves of the nitrogen / sulfur co-doped sodium alginate-based porous carbon materials in Examples 1-5 of this invention; Figure 5 This is a graph showing the relationship between energy density and power density of a symmetrical supercapacitor assembled from nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to Example 1 of the present invention. Figure 6 The symmetrical supercapacitor assembled from nitrogen / sulfur co-doped sodium alginate-based porous carbon material in Example 1 of this invention achieves a performance of 10 A·g -1 Capacity retention rate after 50,000 charge-discharge cycles at high current density. Detailed Implementation
[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0022] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0023] In this invention, unless otherwise specified, the experimental materials and instruments are all conventional experimental materials in the field and can be purchased through commercial channels.
[0024] Example 1 A method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material includes the following steps: S1. Weigh 300 mg of sodium alginate and 300 mg of sodium lignosulfonate, dissolve them in 20 mL of deionized water, and stir for 0.5 h in a constant temperature water bath at 60 °C. Then add 600 mg each of potassium carbonate and ammonium oxalate monohydrate, and continue stirring in a constant temperature water bath at 60 °C for 2.5 h to form a homogeneous mixed solution. Pour the mixed solution into a pre-prepared fixed mold, transfer it to a freeze dryer, and freeze dry at -56 °C for 48 h to obtain sodium alginate-based carbon precursor. S2. Place the sodium alginate-based carbon precursor into a tube furnace and introduce nitrogen gas as a protective atmosphere at a flow rate of 150 mL / min. -1 The heating rate is set to 3℃·min. -1 The sample was first heated to 500℃ and carbonized at this temperature for 0.5 h, then heated to 700℃ and activated at this temperature for 2 h. The activated product was washed with 1M HCl and deionized water until the pH of the filtrate was neutral to remove impurities. Finally, the sample was transferred to an oven and dried at 80℃ to constant weight to remove residual moisture, yielding a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, denoted as SLKN. 122 -700.
[0025] Example 2 This embodiment operates the same as Example 1, except that in S1, the amount of potassium carbonate added is 900 mg, and the amount of ammonium oxalate monohydrate added is 300 mg; in S2, the nitrogen / sulfur co-doped sodium alginate-based porous carbon material is denoted as SLKN. 131 -700.
[0026] Example 3 This embodiment operates the same as Example 1, except that in S1, the amount of potassium carbonate added is 300 mg, and the amount of ammonium oxalate monohydrate added is 900 mg; in S2, the nitrogen / sulfur co-doped sodium alginate-based porous carbon material is denoted as SLKN. 113 -700.
[0027] Example 4 This embodiment is operated the same as in Example 1, except that in S2, the activation temperature is 650℃, and the resulting nitrogen / sulfur co-doped sodium alginate-based porous carbon material is denoted as SLKN. 122 -650.
[0028] Example 5 This embodiment is operated the same as in Embodiment 1, except that in S2, the activation temperature is 750℃, and the resulting nitrogen / sulfur co-doped sodium alginate-based porous carbon material is denoted as SLKN. 122 -750.
[0029] A scanning electron microscope (SEM) was used to characterize the nitrogen / sulfur co-doped sodium alginate-based porous carbon material of Example 1, and the results are shown in Figure 1 , where Figure 1 (a) is the SEM characterization image at a 10 μm scale bar, Figure 1 and (b) is the SEM characterization image at a 5 μm scale bar. It can be seen from Figure 1 that the nitrogen / sulfur co-doped sodium alginate-based porous carbon material has a connected porous structure.
[0030] The nitrogen adsorption method was used to characterize the nitrogen / sulfur co-doped sodium alginate-based porous carbon materials of Examples 1 to 5, and the results are shown in Table 1, Figure 2 and Figure 3 , where Figure 2 is the nitrogen adsorption-desorption isotherm curve, Figure 3 and is the pore size distribution diagram.
[0031] Table 1 Specific surface area, pore volume and pore size of Examples 1-5
[0032] It can be seen from Table 1 that as the activation temperature increases from 600°C to 700°C, the specific surface area and pore volume of the material also increase, indicating that the etching effect of the activating agent is gradually enhanced and a large number of micropores are formed. When the activation temperature is further increased to 750°C, the specific surface area of the material decreases slightly, indicating that at an excessively high temperature, part of the micropore walls are burned through, and the transformation of micropores to mesopores occurs. The ratio of activating agents shows a significant synergistic pore-forming effect on the regulation of the hierarchical pore structure. At an appropriate ratio of potassium carbonate to ammonium oxalate monohydrate of 1:1, due to the synergistic effect of the activating agents, SLKN 122 -700 obtained a high specific surface area (1961.15 m 2 ·g -1 ) and a reasonable pore volume.
[0033] It can be seen from Figure 2 that the isotherms of all samples show the coexistence of Type I and Type IV characteristics. At the low relative pressure stage (P / P0<0.1), the adsorption capacity increases rapidly, showing obvious Type I isotherm characteristics, indicating that a large number of microporous structures exist in the material. As the relative pressure increases (0.4<P / P0<0.9), an obvious H4-type hysteresis loop appears in the isotherm, which indicates that the material contains not only micropores but also a certain number of mesopores. In the high relative pressure region (0.9<P / P0<1), the adsorption curve rises, indicating that there are macropores or irregular pore structures generated by particle accumulation in the material.
[0034] From Figure 3As can be seen, the pore size of all samples is mainly distributed between 0.5-2 nm, verifying their micropore-dominated characteristics. At the same time, broad distribution peaks were also observed in the 2-5 nm region and the region greater than 10 nm, confirming the formation of a hierarchical porous structure (micropore-mesopore-macropore synergy).
[0035] The nitrogen / sulfur co-doped sodium alginate-based porous carbon material prepared in Examples 1-5, acetylene black (conductive carbon black), and polytetrafluoroethylene (binder) were mixed in a mass ratio of 8:1:1. A small amount of anhydrous ethanol was added dropwise and stirred until homogeneous. The mixture was then thoroughly ground to obtain a paste. After the anhydrous ethanol evaporated, the paste was rolled into a long strip and dried at 100°C for 12 hours. The dried electrode strip was then cut into working electrodes with a size of 1 cm × 1 cm. Each electrode was loaded with approximately 2.5 mg of active material. The electrode sheets were pressed onto the current collector foam nickel under a pressure of 10 MPa to obtain the working electrodes. The electrolyte was 6 mol·L⁻¹. -1 KOH, current density 0.5 A·g -1 In the three-electrode system, its electrochemical performance was tested using the constant current charge-discharge method, and the results are as follows: Figure 4 As shown.
[0036] according to Figure 4 The discharge duration is calculated using the following formula for the specific capacitance of the electrode material: , in, C s The specific capacitance of the electrode material (F·g) -1 ), I represents the discharge current (A), Δ t Δ represents the discharge time (s), m represents the mass of the active material loaded on the electrode surface (g), and Δ represents the discharge time (s). V This represents the voltage drop (V) during discharge.
[0037] The nitrogen / sulfur co-doped sodium alginate-based porous carbon materials in Examples 1-5 have specific capacitances of up to 427 F·g. -1 374F·g -1 425F·g -1 358F·g -1 373F·g -1 This indicates that appropriately increasing the temperature (e.g., 700℃) can promote a more complete reaction between potassium carbonate and the carbon skeleton, thereby increasing the specific surface area. Simultaneously, it promotes deep fusion of heteroatoms and the carbon skeleton, inducing more defect sites to generate pseudocapacitance, thus increasing the total capacitance. However, at higher activation temperatures (750℃), excessive etching thins the micropore walls, even causing them to burn through and merge into macropores. This reduces the effective electric double layer surface area, and the significant loss of oxygen-containing functional groups weakens the pseudocapacitance contribution, leading to a decrease in specific capacitance. Therefore, SLKN... 122The sample with a capacitance of -700 exhibited the best performance, at 427.45 F·g. -1 This is because a reasonable ratio of activator and a suitable activation temperature are crucial for constructing a synergistically optimized structure that balances double-layer capacitance and pseudocapacitance.
[0038] The two electrodes prepared in Example 1 with the same active material loading were used as working electrodes, with a loading of 6 mol·L⁻¹. -1 A sandwich-structured symmetrical supercapacitor was assembled using KOH as the electrolyte. The electrochemical performance of the device was measured to evaluate the application potential of the prepared nitrogen / sulfur co-doped sodium alginate-based porous carbon material in supercapacitors. The results are as follows: Figure 5 , Figure 6 As shown. Among them, Figure 5 With a current density of 0.5 A·g -1 Time-energy density-power density relationship graph, Figure 6 For 10A·g -1 Capacity retention rate after 50,000 charge-discharge cycles at high current density.
[0039] The formulas for calculating current density, specific capacitance, energy density, and power density are as follows: in, C scell The specific capacitance of energy storage devices (F·g) -1 ), E d Represents the energy density of energy storage devices (Wh·kg) -1 ), P Indicates its power density (W·kg) -1 ).
[0040] from Figure 5 As can be seen from this, the current density is 0.5 A·g -1 At that time, the specific capacitance of the supercapacitor was 74.8 F·g. -1 The energy density is 14.96 Wh·kg. -1 The corresponding power density is 225 W·kg -1 This performance parameter reaches an advanced level, exceeding the energy density of most carbon-based supercapacitors.
[0041] from Figure 6 As can be seen, after 50,000 charge-discharge cycles, the device retains 83.89% of its initial capacity, demonstrating that the device has high energy density, excellent cycle stability, and reversibility.
[0042] Therefore, this invention employs the aforementioned nitrogen / sulfur co-doped sodium alginate-based porous carbon material, its preparation method, and its application. Through supramolecular self-assembly of sodium alginate and sodium lignin sulfonate, molecular-level uniform composites of carbon source, nitrogen and sulfur source, and activator are achieved. Combined with potassium carbonate and ammonium oxalate monohydrate composite activators, bidirectional pore formation is achieved, simultaneously completing in-situ nitrogen and sulfur co-doping. The resulting porous carbon material possesses a density of 1961 μm. 2 ·g -1 Its high specific surface area and interconnected hierarchical channel structure make it suitable as an electrode for supercapacitors at 0.5 A·g -1 The current density can reach 427 F·g -1 High specific capacitance; after assembling a symmetrical supercapacitor, a capacitance of 14.96 Wh·kg⁻¹ can be achieved. -1 With an energy density of 83.89% after 50,000 long cycles, it exhibits excellent energy storage performance and strong cycle stability. At the same time, the raw material is low-cost biomass, and the preparation process is green and controllable, providing a brand-new preparation idea for high-performance biomass-based energy storage carbon materials.
[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, characterized in that: Includes the following steps: S1. Sodium alginate, sodium lignosulfonate and water are mixed and stirred for the first time. Potassium carbonate and ammonium oxalate monohydrate are added and stirred for the second time. The mixture is then freeze-dried to obtain sodium alginate-based carbon precursor. S2. Under a nitrogen atmosphere, the sodium alginate-based carbon precursor is carbonized, activated, washed, and dried to obtain nitrogen / sulfur co-doped sodium alginate-based porous carbon material.
2. The method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to claim 1, characterized in that: In S1, the mass-volume ratio of sodium alginate, sodium lignosulfonate, and water is 30 mg: 30 mg: 2 mL, and the mass ratio of sodium alginate, potassium carbonate, and ammonium oxalate monohydrate is 1: (1-4): (1-4).
3. The method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to claim 1, characterized in that: In S1, the temperature of the first stirring is 50-70℃ and the stirring time is 0.1-1h; the temperature of the second stirring is 50-70℃ and the stirring time is 2-3h.
4. The method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to claim 1, characterized in that: In S1, the freeze-drying temperature is -56℃ and the freeze-drying time is 48h.
5. The method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to claim 1, characterized in that: In S2, the carbonization temperature is 300-500℃, the carbonization time is 0.1-1h, and the carbonization heating rate is 3-10℃·min. -1 .
6. The method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to claim 1, characterized in that: In S2, the activation temperature is 600-800℃ and the activation time is 1-3h.
7. The method for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material according to claim 1, characterized in that: In S2, the flow rate of nitrogen is 10-150 mL / min. -1 .
8. A nitrogen / sulfur co-doped sodium alginate-based porous carbon material, characterized in that: The material was prepared using the method described in any one of claims 1-7 for preparing a nitrogen / sulfur co-doped sodium alginate-based porous carbon material.
9. An application of a nitrogen / sulfur co-doped sodium alginate-based porous carbon material, characterized in that: The nitrogen / sulfur co-doped sodium alginate-based porous carbon material of claim 8 is applied to the electrode material of a supercapacitor.